Design configuration of encoder and decoder modules for modified double weight (MDW) code spectral amplitude coding (SAC) optical code division multiple access (OCDMA) based on fiber Bragg gratings - Zan, Zuraidah; Syed Junid, Syed Alwee Aljunid; Yaacob, Mohd Hanif; Abdullah, Mohamad Khazani; Shaari, Sahbudin (IEEE, 2005)
In this work, we are proposing the serial and parallel configurations of encoder and decoder modules to encode and decode a new developed spectral amplitude coding (SAC) known as modified double weight (MDW) code for optical code division multiple access (OCDMA) system. This coding scheme is designed in a way to decrease the number of FBGs used in the encoder and decoder modules and to maintain the cross-correlation parameter to 1.